Long-term results (60 months) of anti-VEGF therapy of macular diseases in real clinical practice. Part 1 - E. V. Bobykin; R. V. Buslaev; V. Y. Krokhalev; O. V. Morozova; N. S. Beresneva (Российский офтальмологический журнал)
Purpose: to study long-term (over a 60 months’ follow-up period) results of anti-VEGF therapy for macular diseases in real clinical practice.Materials and methods. We undertook a single-center retrospective uncontrolled cohort study of 169 patients (109 women, 60 men) who received anti-VEGF therapy for eye diseases (ranibizumab, aflibercept). The treatment started between May 2010 and August 2015. The study group included 57 patients who remained under regular observation for 60 months. Of these, 24 cases had “wet” age-related macular degeneration (wAMD), 20 cases had myopic choroidal neovascularization, 10 had macular edema due to retinal vein occlusions and 3 had diabetic macular edema. The remaining 112 patients whose follow-up was discontinued made up the comparison group. We analyzed the dynamic results of clinical and instrumental examination in both groups, as well as data from a phone survey among the comparison group about the reasons for the termination of clinical observation. Statistical analysis of demographic data and treatment results was carried out using the Statistica 13.3 software. Conditions of normality for variables, nonparametric and parametric criteria were determined, and rank analysis of variance was carried out.Results. The patients in the study group were significantly younger (p = 0.0029), had a higher initial (p = 0.0019) and final (p = 0.00027) best corrected visual acuity, and received a significantly greater number of intravitreal injections (p < 0.000001). In contrast, they had a significantly lower rate of therapy intensity factor (the ratio of injections number to the duration of observation in months) over the treatment period (p < 0.000001). In addition, the study group had a significantly lower proportion of men (p = 0.041) and patients with wAMD (p = 0.0010). The reasons for the termination of observation in the comparison group given in the phone survey, were as follows: stopped regular observation / treatment — 57 people (50.9 %), continue treatment in a different clinic — 3 (2.7 %), died — 13 (11.6 %), status unknown — 39 (34.8 %).Conclusion. The data of the main morphological and functional results of treatment of the study group patients, discussion and conclusions will be presented in the second part of this article.